1989
DOI: 10.1111/j.1365-2044.1989.tb11439.x
|View full text |Cite
|
Sign up to set email alerts
|

The pressor response and laryngeal mask insertion

Abstract: SummaryThe pressor response associated with laryngoscopy and tracheal intubation may be harmful to certain patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
56
1
4

Year Published

1992
1992
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 150 publications
(66 citation statements)
references
References 8 publications
5
56
1
4
Order By: Relevance
“…One possible advantage of its use is that insertion of the LMA is associated with a lesser haemodynamic response compared with conventional laryngoscopy and tracheal intubation [3]. To date this has been documented by one study [4], but the authors employed only intermittent measurement of arterial pressure and used an oral airway as part of the technique; this has been shown to be associated with similar cardiovascular responses to those produced by the LMA itself [S], and may have caused difficulty in interpretation of the data. In contrast, Griffin and colleages [6] found no difference in mean systolic arterial pressure and heart rate response between tracheal intubation and LMA insertion.…”
mentioning
confidence: 99%
“…One possible advantage of its use is that insertion of the LMA is associated with a lesser haemodynamic response compared with conventional laryngoscopy and tracheal intubation [3]. To date this has been documented by one study [4], but the authors employed only intermittent measurement of arterial pressure and used an oral airway as part of the technique; this has been shown to be associated with similar cardiovascular responses to those produced by the LMA itself [S], and may have caused difficulty in interpretation of the data. In contrast, Griffin and colleages [6] found no difference in mean systolic arterial pressure and heart rate response between tracheal intubation and LMA insertion.…”
mentioning
confidence: 99%
“…Another study by N. Brande & E.A.F. 5 Clements studied the cardiovascular response induced by laryngoscopy and intubation and that with laryngeal mask airway in 24 and 23 healthy patients respectively. The study showed a maximum mean increase in systolic blood pressure of 17.1% and 8.6% in endotracheal tube & laryngeal mask airway group respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to tracheal intubation and extubation, the use of SADs is associated with more stability in hemodynamics, 15 intracranial pressure, 16 and intraocular pressure. [17][18][19] There is a lower incidence of emergence cough and postoperative sore throat with SADs.…”
Section: Alternative To Tracheal Intubation For Routine Anesthesiamentioning
confidence: 99%